2013
DOI: 10.1128/jvi.00449-13
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Alphavirus TF Protein

Abstract: Here, we validate the findings of Firth and colleagues with respect to the production of the TF protein and begin to characterize the function of TF. Using a mass spectrometry-based approach, we identified TF in purified preparations of both Sindbis and Chikungunya virus particles. We next constructed a panel of Sindbis virus mutants with mutations which alter the production, size, or sequence of TF. We demonstrate that TF is not absolutely required in culture, although disrupting TF production leads to a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(135 citation statements)
references
References 46 publications
5
130
0
Order By: Relevance
“…Interestingly, recent studies have identified a frame-shifted (21 ORF) C-terminal extension of 6K, termed TF. TF was identified within both purified Sindbis virus (SINV) and CHIKV virions, and, although not essential, its deletion led to significant decreases in particle release in cultured mammalian and insect cells without affecting genome replication, particle infectivity or E protein trafficking (Snyder et al, 2013). SINV TF mutants are attenuated in vivo and the protein induces bacterial membrane permeability to a similar degree as 6K.…”
Section: Other Rna Virus Viroporinsmentioning
confidence: 99%
“…Interestingly, recent studies have identified a frame-shifted (21 ORF) C-terminal extension of 6K, termed TF. TF was identified within both purified Sindbis virus (SINV) and CHIKV virions, and, although not essential, its deletion led to significant decreases in particle release in cultured mammalian and insect cells without affecting genome replication, particle infectivity or E protein trafficking (Snyder et al, 2013). SINV TF mutants are attenuated in vivo and the protein induces bacterial membrane permeability to a similar degree as 6K.…”
Section: Other Rna Virus Viroporinsmentioning
confidence: 99%
“…64). Translation of the structural polyprotein continues, generating a majority product, E3-E2-6K-E1, and a minor product, E3-E2-TF, due to ribosomal frameshifting (67,68). A signal sequence present at the copies) that encapsidates genomic RNA (64,69).…”
Section: Ecology and Epidemiologymentioning
confidence: 99%
“…Four essential nonstructural proteins (nsP1, 2, 3, and 4) constitute the RNA replicase (Table 2) and are encoded by the 5′ two-thirds of the genome (65,66). The 3′ ORF is translated from a subgenomic positive-strand mRNA and encodes six proteins (Table 2), including three major structural proteins (capsid, E1, and E2) (64,(66)(67)(68). The CHIKV virion is formed by a lipid bilayer envelope tightly associated with an icosahedral nucleocapsid shell (240 capsid of CHIKV disease (Figure 1 and refs.…”
Section: Ecology and Epidemiologymentioning
confidence: 99%
“…In addition, recent studies have identified important roles for changes in nsP3, TF, and the 5' nontranslated region that influence neuronal replication and alter virulence [28][29][30]. Neuronal maturation leads to restriction of Sindbis virus replication.…”
Section: Role Of Virus Strainmentioning
confidence: 99%